2016
DOI: 10.18857/jkpt.2016.28.6.349
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neck Flexor and Sternocleidomastoid Muscle Thickness Change in Persons with No Current Neck Pain using Rehabilitative Ultrasonograpic Imaging

Abstract: Purpose: The purpose of the study was to investigate the thickness of deep neck flexors (DNF) and sternocleidomastoid muscle (SCM) bilaterally during deep neck flexor endurance test using ultrasonography images. Methods: Healthy volunteers (n= 22), 20-25 (mean 22.2) years old, were recruited for the study. Participants were asked to perform the craniocervical flexion test (CCFT) in a seated position to measure deep neck flexor endurance. The thickness of DNF and SCM was assessed bilaterally and was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies conducted on patients with neck pain reported smaller cross-sectional area (CSA) of LCo (22), altered motor control strategy including reduced activity of DNF muscles and increased activity of superficial neck flexor muscles (SCM) during CC flexion (23). Increased activity of superficial neck flexor muscles may be a compensatory mechanism for reduced activity of DNF muscles (24). In this study we used 50% of maximum isometric contraction of CC flexion because, according to the results of previous studies there was not significant changes in muscle thickness in contraction levels above 50% of maximum isometric contractions (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies conducted on patients with neck pain reported smaller cross-sectional area (CSA) of LCo (22), altered motor control strategy including reduced activity of DNF muscles and increased activity of superficial neck flexor muscles (SCM) during CC flexion (23). Increased activity of superficial neck flexor muscles may be a compensatory mechanism for reduced activity of DNF muscles (24). In this study we used 50% of maximum isometric contraction of CC flexion because, according to the results of previous studies there was not significant changes in muscle thickness in contraction levels above 50% of maximum isometric contractions (17).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle thickness change during CC flexion has been neglected in previous studies. This parameter is important because muscle thickness change can be informative about muscle contraction pattern (24) and more muscle thickness changes express more muscle activity (11). Measurement of muscle thickness change of cervical muscles can indicate stabilizing role of these muscle, because deep neck muscles are more active in contraction state relative to resting state to provide stability of the cervical spine (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation